PROSES PEMBELAJARAN METODE DEMONSTRASI DALAM MATERI WUDHU PADA KELAS IV DI SDN 1 KAPAR, KECAMATAN MURUNG PUDAK, KABUPATEN TABALONG - Nurhayati Nurhayati (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research was motivated by Islamic religious education learning in ablution material in class IV at SDN 1 Kapar, with the hope that students could achieve their learning goals as well as possible. However, in reality, various things can hinder the achievement of these learning goals. There are several students who have not been able to achieve the learning objectives in the ablution material because they have difficulty learning in learning activities, even though the ablution material has been taught in class II, at that time the teacher used the lecture method in learning, besides that the learning was also carried out online via WA (WhatsApp). So the aim of the research is to determine the process and supporting and inhibiting factors for learning the demonstration method in ablution material in class IV at SDN 1 Kapar, Murung Pudak District, Tabalong Regency. Researchers use field research with a qualitative descriptive approach, while data collection techniques are carried out starting from observation, interviews, documentation and data analysis, as well as data analysis techniques starting from data reduction, data display and drawing conclusions. Thus, the results of the research state that the demonstration method learning process on ablution material at SDN 1 Kapar has been carried out according to the planned learning procedures and students' understanding has increased, from previously not understanding the correct way to perform ablution. Meanwhile, the supporting and inhibiting factors come from students, teachers, time allocation, and tools and facilities.